Subtract 1/2(z+4)−3(1/4z+1) . Use fractions in final form

2 answers

To subtract the expressions, let's expand and simplify each term separately:

First, let's expand 1/2(z + 4):
1/2(z + 4) = 1/2 * z + 1/2 * 4 = 1/2z + 2

Next, let's expand 3(1/4z + 1):
3(1/4z + 1) = 3 * 1/4z + 3 * 1 = 3/4z + 3

Now, let's subtract the two expressions:
1/2z + 2 - (3/4z + 3)

Next, let's get a common denominator for the fractions (which is 4):
1/2z + 2 - (3/4z + 3) = 1/2z + 2 - (3/4z + 3) * 2/2

Now, let's simplify the expression:
= 1/2z + 2 - (6/8z + 6/2)
= 1/2z + 2 - 6/8z - 3

Next, let's combine like terms:
= (1/2z - 6/8z) + (2 - 3)
= (4/8z - 6/8z) + (-1)
= (-2/8z) + (-1)

Now, let's simplify the expression further:
= -1/4z - 1

Therefore, the final simplified form of the expression is -1/4z - 1.
what is the answer